VATS (Video Assisted Thoracoscopic Surgery) Pleural Biopsy in the Diagnosis of Unexplained Pleural Effusion (Journal of Bangladesh College of Physicians and Surgeons, 2023)
Introduction:An unexplained pleural effusion is a difficult diagnostic dilemma that needs further histological study for a definitive etiological diagnosis. Video assisted thoracoscopic (VATS) pleural biopsy is a minimally invasive procedure that could resolve this problem. The study is conducted to determine the efficacy of VATS pleural biopsy in the diagnosis of unexplained pleural effusion.Methods: This  cross-sectional  study  was  to  investigate our experience  of VATS pleural biopsy for unexplained pleural effusion which  was  conducted  at  our center.   All   patients   who   underwent   VATS pleural biopsy for unexplained pleural effusion   during   the   period of January 2019 to December 2019 were included in the study. Epidemiological, clinical, radiological & histopathological data of the patients were collected and analyzedResults: The overall diagnostic yield of VATS pleural biopsy in our study was 95%. Malignancy was the most common histological diagnosis for unexplained pleural effusion followed by tuberculosis. In patients with malignant effusion, metastatic adenocarcinoma was commonly observed finding followed by metastatic squamous cell carcinoma. Minor complications related to the procedure were noticed with no mortality.Conclusion: VATS pleural biopsy has high definitive diagnostic accuracy in the evaluation of unexplained pleural effusions.J Bangladesh Coll Phys Surg 2023; 41: 141-149